PERAN BAITUL MAAL SEBAGAI LEMBAGA KEUANGAN MIKRO SYARIAH DALAM MENDUKUNG KEBUTUHAN PEREKONOMIAN MASYARAKAT INDONESIA - Efendi, Erizal Candra; Ahmad Wira (MBISKU: Jurnal Manajemen Bisnis dan Keuangan, 2025)
This study analyzes the role of Baitul Maal as a sharia microfinance institution in meeting the economic needs of the community, especially in providing access to financing in accordance with sharia principles. Using qualitative methods, this study found that Baitul Maal plays an important role in improving the economic and social welfare of the community. Baitul Maal not only provides financing solutions for micro, small and medium enterprises (MSMEs) that are not reached by conventional financial institutions, but also contributes to poverty alleviation and the achievement of sustainable development goals (SDGs). However, the study also identified several challenges in program management, such as limited resources and lack of synergy with other Islamic financial institutions. This research recommends strengthening strategic partnerships and innovations in financial products and services to increase the effectiveness of Baitul Maal's role in the future.